Dynamic Consensus for Deformable Body Centroid Estimation - Pardina Quirós, Sergio; Aragüés Muñoz, Rosario; López Nicolás, Gonzalo (Jornada de Jóvenes Investigadores del I3A, 2025)
We study a consensus algorithm to enable multiple independent agents to collectively estimate the centroid of a moving, deformable body. Each agent has only partial information about the system in the form of an individual reference signal. This is performed in a fully distributed manner, without centralized or hierarchical communication. We also provide a mathematical expression for the upper bound of the expected error.